PENGARUH PENERAPAN MODEL PEMBELAJARAN PAIKEM GEMBROT TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS - Nila Utami; M. Djahir Basir; Fitriyanti Fitriyanti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2015)
The research problem is that whether there is difference in the effect of the application of PAIKEM GEMBROT Learning Model to the students’ learning Motivation on Social science Subject at SMP Negeri 45 Palembang. The population takes all students of class VIII SMP Negeri 45 Palembang. By using the Cluster Random Sampling, the students of class VII.4 are selected as the experiment class and class VII.5 as the control class. Data analysis technique used is the t-test invitation significant level (α = 0.05). Based on the data analysis, it obtained t count equal to 6.62 and 1.99 t table so the hypothesis proposed in this study may be accepted, that there are differences in the effect of the application of learning models PAIKEM GEMBROT with thematic learning model to the motivation of learners in the social science studies. It is therefore advisable for teachers to use learning model PAIKEM GEMBROT as an alternative learning in increasing the motivation of learners.